Symbiotic relationship from yacon extract (Smallanthus sonchifolius) and Lactobacillus plantarum against Escherichia coli - Vegas, Carlos A. (2013)
The development of strategies for a better control of gut microbiota have increased the interest in associate prebiotics and probiotics, in a symbiotic state, in order to reduce the presence of pathogenic microorganisms. The aim of this work was to study the symbiotic effect between Smallanthus sonchifolius (yacon) extract and Lactobacillus plantarum against the growth of enteropathogenic Escherichia coli. To do this, the best concentration of yacon extract for the growth of L. plantarum and their prebiotic effect were previously done. The microbial growth kinetic was determined by optical density, counting by microscope and viability in plate. L. plantarum presented an optimal growth at 15°Brix, reaching 109 cells/mL; whereas E. coli remained at low population levels. The combination of yacon extract and L. plantarum totally inhibited the growth of enteropathogenic E. coli at 16 h of incubation.